Cognitive Disorders 2019
DOI: 10.5772/intechopen.75887
|View full text |Cite
|
Sign up to set email alerts
|

The Hypothalamus in Alzheimer’s Disease: A Golgi and Electron and Microscope Study

Abstract: Alzheimer's disease is a progressive irreversible neurodegenerative disorder, characterized by gradual decline of mental faculties including learning capacity, emotional and behavioral alterations, serious decline of motor skills, and dysfunction of the autonomic nervous system with disruption of circadian rhythms. Among the potential modifiable risk factors diabetes and obesity may play a considerable role in the pathogenetic background of the disease. We describe some of the morphological alterations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 109 publications
1
27
1
Order By: Relevance
“…Baloyannis et al demonstrated in early-onset AD cases that several hypothalamic nuclei (suprachiasmatic, supraoptic, and paraventricular) showed pathological hallmarks including reduced neuronal population, dystrophic axons, abnormal Golgi, and synaptic spines without the characteristic AD pathology (neurofibrillary tangles and senile plaques) in these areas. 42 These alterations were present in the hypothalamus of brains from 12 sAD patients with clear sAD clinical pathological diagnosis suggesting that these morphological hypothalamic neuron alterations could appear very early in AD prior to A and tau deposition. 12 Many authors recognize the hypothalamus as the most important autonomous nervous system engine, but others included other limbic structures such as the hippocampus.…”
Section: Sporadic Alzheimer's Diseases (Sad) and The Predementia Perimentioning
confidence: 87%
See 1 more Smart Citation
“…Baloyannis et al demonstrated in early-onset AD cases that several hypothalamic nuclei (suprachiasmatic, supraoptic, and paraventricular) showed pathological hallmarks including reduced neuronal population, dystrophic axons, abnormal Golgi, and synaptic spines without the characteristic AD pathology (neurofibrillary tangles and senile plaques) in these areas. 42 These alterations were present in the hypothalamus of brains from 12 sAD patients with clear sAD clinical pathological diagnosis suggesting that these morphological hypothalamic neuron alterations could appear very early in AD prior to A and tau deposition. 12 Many authors recognize the hypothalamus as the most important autonomous nervous system engine, but others included other limbic structures such as the hippocampus.…”
Section: Sporadic Alzheimer's Diseases (Sad) and The Predementia Perimentioning
confidence: 87%
“…22,27 This opinion is supported by experimental evidence using injured and/or stimulated animal models and probably is based on limbic system lesions (hippocampus, hypothalamus, and several brain stem nuclei), which represents a primitive hub controlling body functions regulated by the autonomous nervous system. 27,32,41,42 The hypothalamus integrates the majority of basic life functions: energy metabolism (feeding); fluid and electrolyte balance (drinking); thermoregulation, fever responses; wake-sleep cycles; emergency response to stressors; reproduction (mating, pregnancy, birth); 32 and body immunity. 25,27,28,30 The integrated functions of nervous and immune systems could be affected during preclinical and early prodromal sAD, and later on during MCI and dementia stage of sAD, as hypothalamus and limbic structures have early AD lesions leading to loss of the nervous system and immune system homeostasis 26,44 (Figure 2).…”
Section: Hypothalamic Dysfunctions In Sad May Preclude Immunity Altermentioning
confidence: 99%
“…Therefore, it is remarkable that salivary Lf levels will not decrease in other dementia such as FTD. A possible explanation could be that the hypothalamic region, that controls body innate immunity, [49] is affected in AD [50][51][52][53], but not in FTD. In addition to amyloid plaques and neurofibrillary tangles, functional studies suggest that hypothalamic dysfunction is a common event in AD, often early in the course of disease [51].…”
Section: Discussionmentioning
confidence: 99%
“…The secretion of salivary proteins is controlled by cholinergic parasympathetic nerves that release acetylcholine, evoking the secretion of saliva by acinar cells in the salivary gland [55]. These parasympathetic nerves are connected with the hypothalamus [50][51][52][53]. We propose that early hypothalamic Aβ accumulation may disrupt hypothalamic function affecting salivary gland regulation that ultimately results in reduced salivary Lf secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathological alterations in the MMN are rare or even entirely absent in vascular dementia (VD) patients (9). Although in Alzheimer's disease (AD) this nucleus shows some neuritic plaques, diffuse Aβ plaques and tangles, their extension is significantly less than in the cortex or the adjacent tuberomamillary nucleus (TMN) (10,11). Previous studies that used the Golgi complex (GC) size as a parameter of the neuronal metabolic activity showed decreased metabolic activity of the TMN neurons in both, AD and VD (3,12,13), while in the MMN no decline in metabolic activity was found, either in VD or AD using this parameter (6,13).…”
Section: Introductionmentioning
confidence: 99%